CGRP and Migraine: What Have We Learned From Measuring CGRP in Migraine Patients So Far? - Kamm, Katharina (Frontiers in Neurology, 2022)
The multi-functional neuropeptide calcitonin gene-related peptide (CGRP) plays a major role in the pathophysiology of migraine. The detection of elevated CGRP levels during acute migraine headache was the first evidence of the importance of the peptide. Since then CGRP has been detected not only during spontaneous and experimentally induced migraine attacks but also interictally. The detection of CGRP in peripheral blood shows conflicting results. In this respect, alternative detection methods are needed and have been already proposed. This article summarizes what we have learned from studies investigating CGRP in jugular and peripheral blood and reviews the latest state of research concerning the detection of CGRP in saliva and tear fluid as well as their contribution to our understanding of migraine pathophysiology.